An 8-Week Knee Osteoarthritis Treatment Program of Hyaluronic Acid Injection, Deliberate Physical Rehabilitation, and Patient Education is Cost Effective at 2 Years Follow-up: The OsteoArthritis Centers of AmericaSM Experience. Issue 7 (January 2014) - Miller, Larry E.; Block, Jon E.
Numerous nonsurgical interventions have been reported to improve symptoms of knee osteoarthritis (OA) over the short term. However, longer follow-up is required to accurately characterize outcomes such as cost effectiveness and delayed arthroplasty. A total of 553 patients with symptomatic knee OA who previously underwent a single 8-week multimodal treatment program were contacted at 1 year ( n = 336) or 2 years ( n = 217) follow-up. The percentage of patients who underwent knee arthroplasty was 10% at 1 year and 18% at 2 years following program completion. The treatment program was highly cost effective at 12, 800 per quality-adjusted life year at 2 years. Cost effectiveness was maintained under a variety of plausible assumptions and regardless of gender, age, body mass index, disease severity, or knee pain severity. In summary, a single 8-week multimodal knee OA treatment program is cost effective and may lower knee arthroplasty utilization through 2 years follow-up.